2017
DOI: 10.1071/py16038
|View full text |Cite
|
Sign up to set email alerts
|

Using logic models to enhance the methodological quality of primary health-care interventions: guidance from an intervention to promote nutrition care by general practitioners and practice nurses

Abstract: The methodological designs underpinning many primary health-care interventions are not rigorous. Logic models can be used to support intervention planning, implementation and evaluation in the primary health-care setting. Logic models provide a systematic and visual way of facilitating shared understanding of the rationale for the intervention, the planned activities, expected outcomes, evaluation strategy and required resources. This article provides guidance for primary health-care practitioners and research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…Nurses were found to be unaware of their roles and felt incapable of providing nutritional care (step 1). This is in accordance with other studies, which demonstrated that nurses were unaware of their nutritional roles, demonstrated low self-efficacy, and lacked nutritional knowledge [41,42] and education [43,44]. Since nutrition belongs to the core of basic nursing care [28,45,46], nurses need to be educated on their crucial roles regarding nutrition to ensure that patients are properly fed.…”
Section: Discussionsupporting
confidence: 89%
“…Nurses were found to be unaware of their roles and felt incapable of providing nutritional care (step 1). This is in accordance with other studies, which demonstrated that nurses were unaware of their nutritional roles, demonstrated low self-efficacy, and lacked nutritional knowledge [41,42] and education [43,44]. Since nutrition belongs to the core of basic nursing care [28,45,46], nurses need to be educated on their crucial roles regarding nutrition to ensure that patients are properly fed.…”
Section: Discussionsupporting
confidence: 89%
“…In the context of limited public access to dietitians for chronic disease management, strategies for ongoing support to patients to implement long-term behaviour change required to sustain a MDP are needed. Enhanced use of technology and telehealth [76] as well as training of other primary care practitioners [77] could be useful strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Similar approaches have been used in a range of disciplines and topics, from health systems development in post-conflict societies, 27 to exploring the association between nurse staffing levels and skill mix with patient safety and outcome, 28 and to enhancing the methodological quality of primary health-care interventions. 29 As more research is conducted on AHDs, we anticipate that our existing logic model can be further adapted, improved, and tested.…”
Section: Discussionmentioning
confidence: 99%